Bio‐based polyurethane‐graphene composites for adhesive application. (2nd January 2023) - Tiwari, Shivam; Chhaunker, Sanjai; Maiti, Pralay
Abstract: Natural oil‐based polyurethanes are prepared through solvent‐less and easily processable approach for adhesive applications. The polyurethane is optimized through varying the volume fractions of the precursors which was then confirmed through the different analyses to achieve the better combination for composite formation with graphene. The graphene‐polyurethane composites are processed in a simple hand mixing process with different graphene loadings and the role of the addition of graphene is studied using different analyses. The addition of graphene and the interaction with the polymer is well established through structural and thermal studies. The increase in the mechanical property with the addition of graphene to adequate amount at room temperature confirms better interfacial interaction with the polymer. The maximum peel strength obtained for the PU is around 1.05 N/mm, which supports the applicability of the prepared material for adhesive‐based applications. Abstract : Wrapping of graphene with crosslinked polyurethane.